Mexican drought: an observational modeling and tree ring study of variability and climate change - Seager, R.; Ting, M.; Davis, M.; Cane, M.; Naik, N.; Nakamura, J.; Li, C.; Cook, E.; Stahle, D. W. (eScholarship, University of California, 2009)
Variability of Mexican hydroclimate, with special attention to persistent drought, is examined using observations, model simulations forced by historical sea surface temperature (SST), tree ring reconstructions of past climate and model simulations and projections of naturally and anthropogenically forced climate change. During the winter half year, hydroclimate across Mexico is influenced by the state of the tropical Pacific Ocean with the Atlantic playing little role. Mexican winters tend to be wetter during El Nino conditions. In the summer half year northern Mexico is also wetter when El Nino conditions prevail, but southern Mexico is drier. A warm tropical North Atlantic Ocean makes northern Mexico dry and southern Mexico wet. These relationships are reasonably well reproduced in ensembles of atmosphere model simulations forced by historical SST for the period from 1856 to 2002. Large ensembles of 100 day long integrations are used to examine the day to day evolution of the atmospheric circulation and precipitation in response to a sudden imposition of a El Nino SST anomaly in the summer half year. Kelvin waves propagate east and immediately cause increased column-integrated moisture divergence and reduced precipitation over the tropical Americas and Intra-America Seas. Within a few days a low level high pressure anomaly develops over the Gulf of Mexico. A forced nonlinear model is used to demonstrate that this low is forced by the reduced atmospheric heating over the tropical Atlantic-Intra-America Seas area. Tree ring reconstructions that extend back before the period of instrumental precipitation data coverage are used to verify long model simulations forced by historical SST. The early to mid 1950s drought in northern Mexico appears to have been the most severe since the mid nineteenth century and likely arose as a response to both a multiyear La Nina and a warm tropical North Atlantic. A drought in the 1890s was also severe and appears driven by a multiyear La Nina alone. The drought that began in the 1990s does not exceed these droughts in either duration or severity. Tree ring records extending back to the fourteenth century suggest that the late sixteenth century megadrought may have been the longest drought to have ever affected Mexico. While the last decade or so in north and central Mexico has been drier than preceding decades, the associated continental pattern of hydroclimate change does not fit that which models project to occur as a consequence of rising greenhouse gases and global warming. However, models robustly predict that Mexico will dry as a consequence of global warming and that this drying should already be underway. At least for now, in nature, this is likely obscured by strong natural atmosphere-ocean variability.